I’ll be your mirror. Documentario italiano contemporaneo e cultura social - Ravesi, Giacomo (Mediascapes journal, 2019)
The essay aims to analyze some emblematic cases of contemporary Italian documentaries in which the use of social photography and systems of computer communication and instant messaging (Skype, WhatsApp, Facebook, Instagram, Twitter, etc.) are integrated into the forms and documentary practices, activating a transformation process of consolidated representative and communicative logics. Recent films such as Jointly Sleeping In Our Own Beds (2017, Saverio Cappiello), Uozzap (2018, Federico Iris Osmo Tinelli) and Selfie (2019, Agostino Ferrente) are based on the relationship with media devices and technology, combining self-portraits, participative and collective forms of identity. These are works in first person narrative that rewrite the cinematographic subjectivity, in tune with the social culture of community sharing, oscillating between the logic of selfie and those of the net. The narcissistic exhibition of the contemporary audiovisual system takes on the appearance of a social mask in films, where the image literally becomes a membrane of relationship and contact, that reproduces the faces of the protagonists imprisoning them in the frames and crosses their gazes like in a closed-loop video installation. In these films the screen, the mirror and the camera become the same medium: conceptual devices unified in an autobiographical form linked to the evolution of media systems of self-images circulation. The intimate dimension of the story thus assumes a theoretical tension, witnessing the evolution of the communicative and relational conditions among individuals mediated by the technology of the screens. Camera-look, first-person narrative, the collective sharing of the perspective make clear a new expressive pressure between public and private, in which the testimonial instance of the documentary story involves incessantly in the relational rewriting of digital media, imposing a new modalities of dialogue between "I", "us" and "others". A sense of identity and of community membership in renewal, which social photography and contemporary documentary are developing together.